PENGUATAN KEWARGAAN MELALUI LITERASI BUDAYA: MENJALIN HARMONI SOSIAL DI ERA DIGITAL - Muh. Nana Supriatna; Cucu Atikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to understand the challenges and opportunities in developing cultural and civic literacy in the digital era and provide recommendations for the future. The research method used was descriptive qualitative by conducting a literature search to collect actual and in-depth information. The results show that the main challenges in developing cultural literacy are exposure to false information and provocative content, limited access to cultural literacy education, and lack of understanding and awareness of the importance of cultural and civic literacy. However, technology also provides opportunities in developing cultural literacy by allowing greater access to information and cultures from different parts of the world. Recommendations for the future include increasing the knowledge and mentoring of young people on the ethical and wise use of information technology, as well as the optimal utilisation of technology to enhance civic participation and quality. The study concludes that cultural and civic literacy play an important role in facing the challenges of globalisation and the development of information technology. The research recommendations emphasise the need to increase awareness of cultural and civic literacy, as well as the wise use of technology to strengthen civic participation and identity in the digital era.